THE IDENTIFICATION OF RISK FACTORS THAT PREDICT OCCULT CYSTOBILIARY COMMUNICATION IN LIVER HYDATID CYSTS (Iraqi Journal of Medical Sciences, 2017)
Background: Post-operative biliary leakage in patients with liver hydatid diseases is still a major problem especially after conservative surgery. Radiologic and intraoperative findings may not be helpful to detect occult biliary communications in asymptomatic patients.Objective: To identify the risk factors to predict occult cystobiliary communications (CBC) preoperatively to avoid development of biliary leakage after surgery.Methods: This prospective study conducted at the Gastroenterlogy and Hepatology Teaching Hospital in Medical City, Baghdad from the 1st of December 2013 to the 29th of March 2016. Clinical assessment, laboratory tests and imaging studies were under taken for 85 patients with uncomplicated liver hydatid cysts. Endocystectomy and or partial pericystectomy were undertaken. Post-operative follow up and management of biliary leakage for those with cysto-biliary communication not detected intra operatively. Data were analyzed to predict risk factors for occult CBC.Results: Of the 85 patients, 64 patients had no evidence of CBC neither intra nor postoperative, while the remaining 24 patients had an occult CBC, that have been discovered during operation or evident in the following days. Significant clinical predictors of communication were cyst size ? 10 cm, elevated total serum bilirubin (TSB) and gamma glutamyl transferase (GGT) (P < 0.001). Other findings were associated more with patients having CBC than those without, including high white blood cell count (WBC), alkaline phospatase (ALP), aspartate transaminase (AST) and alanine transaminase (ALT) levels. Nine of 13 patients who developed post-operative bile leak stopped spontaneously, the other 4 patients mandate endoscopic retrograde cholangiopancreatgraphy (ERCP) to close their fistulas.Conclusion: Awareness about the risk factors for CBC can predict preoperative diagnosis of occult CBC. Endoscopic biliary interventions should be considered as a part of complementary treatment of those cases with refractory CBC and to be discussed in patients’s consent preoperatively.Keywords: Liver hydatid cyst, cystobiliary communication, biliary leakage. Citation: Abdul Hassan BA. The identification of risk factors that predict occult cystobiliary communication in liver hydatid cysts. Iraqi JMS. 2017; Vol. 15(3): 288-296. doi: 10.22578/IJMS.15.3.11
Keywords: Liver hydatid cyst; cystobiliary communication; biliary leakage